Interpretation of The Verses Tolerance Comperative Study According to Hamka and Quraish Shihab - Sami; Yeti Dahliana; Saifudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the verses of the Quran with the interpretation of Haji Abdul Malik Karim Amrullah (HAMKA) and Quraish Shihab. Hamka with Tafsir Al-Azhar and Quraish Shihab with Tafsir Al-Misbah. The plural Indonesian nation encourages its people to live in harmony, especially between religious communities. So tolerance is a very important attitude that must be possessed and become the personality of the Indonesian nation itself. The principles of religious beliefs must not be sacrificed for the sake of tolerance, nor should tolerance be sacrificed for the sake of religious beliefs. The Al-Qur'an has explained that we should look after each other's houses of worship, even if they belong to non-Muslims and do not comply with Islamic teachings. So this research will focus on the interpretation of the tolerance verse using interpretations from Hamka and Quraish Shihab. This research is a type of library research because this research is theoretical and philosophical in nature. The approach used by researchers is a sociological approach. The primary data sources for this research are the Tafsir al-Azhar Book from Hamka's interpretation and the Tafsir al-Misbah Book from Quraish Shihab's interpretation. The method used to collect data in this research is documentation which is carried out by digging and searching for documents from pre-existing data sources. The results of this research found that Hamka's interpretation of the tolerance verses has unique characteristics in its implementation in human life, while Quraish Shihab in interpreting the tolerance verses focuses on the basic things that underlie humans in their actions.